Zonificación De La Amenaza Por Avenidas Torrenciales En El Municipio De La Montañita Caquetá (2023)
Torrential floods usually occur due to the excessive increase of rainfall in areas of steep and unstable slopes, one of the main factors is the phenomenon of land transformations, where the land has not been adapted to the proper use and when found within streams, its material is depressed and combined with the flow causing disasters.